A weak alkaline cleaning agent for FA fiber array ultrasonic and a cleaning method thereof

CN122979045APending Publication Date: 2026-10-27SHENZHEN FISHER NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611113024.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

工业上亦存在以烷基苯磺酸钠、脂肪醇聚氧乙烯醚类为主表面活性剂的中性清洗剂,但对树脂残胶与嵌入式研磨粉复合污垢清除率低于70%

Benefits of technology

1、本申请通过两性N-酰基谷氨酸钠与谷氨酸衍生物在pH9.0-10.0条件下构建pH响应型纤维状胶束体系,数均粒径42.3nm,PDI0.132,其纳米级尖端可靶向渗透FA阵列微米级缝隙,从内部破坏复合污垢附着力,复合污垢清除率达99.5%以上;通过乙二胺二琥珀酸三钠与葡萄糖酸钠双配体协同螯合,将游离Ca2+/Fe3+浓度控制在<0.1ppm,阻断金属离子再沉积,配合苯并三氮唑缓蚀保护,使端面Ra变化<0.02nm、腐蚀深度<0.5nm,实现基材100%无损。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of cleaning agent, especially to a kind of FA fiber array ultrasonic special weak alkaline cleaning agent and its cleaning method.The cleaning agent is composed of the following components: amphoteric N-acetyl glutamic acid sodium 5.0-8.5wt%, glutamic acid derivative 3.0-6.0wt%, ethylenediamine disuccinic acid trisodium 1.5-4.0wt%, sodium gluconate 2.0-5.0wt%, corrosion inhibitor 0.2-1.5wt%, and the rest is deionized water, the pH value of the cleaning agent is 9.0-10.0.Each component is added in turn by step-by-step dissolution method to prepare FA fiber array ultrasonic special weak alkaline cleaning agent, and the cleaning effect of high efficiency, substrate non-damage and environmental safety is achieved under the conditions of ultrasonic power density 0.3-0.6W / cm 2 , frequency 40kHz, temperature 35-45℃ for 60-90s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cleaning agent technology, and in particular to a weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber arrays and its cleaning method. Background Technology

[0002] Fiber Arrays (FA) are core precision components in optical communication modules, and the cleanliness of their end faces directly determines optical coupling efficiency and transmission reliability. After grinding, the bottom of the V-groove of the FA fiber array retains a large amount of composite dirt composed of embedded grinding powder (mainly SiC, Al2O3, etc.) and epoxy resin residue, requiring ultrasonic cleaning before subsequent coating or encapsulation processes. Currently, FA fiber array end face cleaning commonly uses strongly alkaline (pH>12) sodium hydroxide or sodium carbonate systems, fluorinated surfactant complex systems, or organic solvents (such as acetone, isopropanol) combined with ultrasonic cleaning. Mainstream processes assess cleanliness according to IEC 61300-2-4 standards, focusing on controlling particulate residue (≥5μm) and organic residue (detected by FTIR or XPS). Industrially, neutral cleaning agents with sodium alkylbenzene sulfonate and fatty alcohol polyoxyethylene ethers as main surfactants also exist, but their removal rate of resin residue and embedded grinding powder composite dirt is less than 70%.

[0003] The main problems faced by existing technologies are: strong alkaline systems easily corrode the metal positioning grooves (stainless steel / nickel alloy) and glass / quartz end faces in the FA array, resulting in an increase in surface roughness Ra > 0.8 nm; organic solvents evaporate quickly, are difficult to control humidity, and have excessive VOC emissions, and have poor dissolving ability for polar resin residues; neutral surfactant micelles have no pH response, cannot achieve targeted penetration into dirt gaps, have high residue rates, and easily cause a decrease in the adhesion of subsequent coatings. Existing patent (CN 101795784 B) uses a compound system of organic solvent, propylene glycol ether, and isopropanol, which reduces ion residue, but the strong solvent corrodes the adhesives (bonding fiber V-groove bottom plate and cover plate) at the head and tail of the FA fiber array; another solution (CN1262629C) uses a compound system of surfactant, solvent, and sodium tripolyphosphate, which contains phosphorus and is not environmentally friendly; none of the above solutions solve the problem of metal ion redeposition after cleaning, and the Ca in the rinsing water is high. 2+ / Fe 3+ Residues >0.5ppm will cause dry spots.

[0004] Meanwhile, optical device cleaning is facing mandatory compliance pressure from EU REACH, RoHS, halogens, and China's "Limits of Volatile Organic Compounds in Cleaning Agents"; the mass production of 5G optical modules places higher demands on the cleaning yield (>99.95%) and single-chip cleaning time (<90s) of FA arrays; in response to the above-mentioned technologies, there is an urgent need in this field to develop a weakly alkaline ultrasonic cleaning agent and its cleaning method specifically for FA fiber arrays to solve the above technical problems. Summary of the Invention

[0005] To achieve the desired effects of high permeability, substrate compatibility, and environmental safety in FA fiber array cleaning agents, this application provides a weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber arrays and its cleaning method.

[0006] In the first aspect, this application provides a weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber optic arrays, employing the following technical solution: A weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays, comprising the following components by weight percentage: Sodium amphoteric N-acylglutamate 5.0-8.5 wt%; Glutamic acid derivatives 3.0-6.0 wt%; Trisodium ethylenediaminedisuccinate 1.5-4.0 wt% Sodium gluconate 2.0-5.0 wt%; Corrosion inhibitor 0.2-1.5 wt%; The remainder is deionized water; The glutamic acid derivative is either L-glutamic acid methyl ester hydrochloride or L-glutamic acid ethyl ester hydrochloride; The cleaning agent has a pH value of 9.0-10.0.

[0007] The above technical solution utilizes amphoteric N-acylglutamate sodium salt and glutamate derivatives to construct a pH-responsive fibrous micelle system at pH 9-10. Its nanoscale tips can target and penetrate the micron-level gaps in the FA array, disrupting the adhesion of complex dirt from within. The mild alkaline selective hydrolysis of resin residues by the glutamate derivatives avoids corrosion of the glass / quartz end faces and metal positioning grooves by strong alkalis. The synergistic chelation of trisodium ethylenediamine disuccinate and sodium gluconate dual ligands releases free Ca2+. 2+ / Fe 3+ The concentration is controlled at <0.1ppm to block redeposition; the corrosion inhibitor further controls the corrosion depth to <0.5nm. The four components work synergistically to achieve high permeability, substrate compatibility, and environmental safety.

[0008] Preferably, the FA fiber optic array ultrasonic-specific weakly alkaline cleaning agent is composed of the following components by weight percentage: Amphoteric N-acylglutamate sodium salt 6.2-7.8 wt% Glutamic acid derivatives 3.8-5.2 wt%; Trisodium ethylenediaminedisuccinate 2.2-3.0 wt%; Sodium gluconate 3.0-4.0 wt%; Corrosion inhibitor 0.5-1.0 wt%; The remainder is deionized water; The glutamic acid derivative is either L-glutamic acid methyl ester hydrochloride or L-glutamic acid ethyl ester hydrochloride; The cleaning agent has a pH value of 9.2-9.8.

[0009] Preferably, the amphoteric N-acylglutamate sodium salt is N-lauroyl-L-glutamate sodium salt, and the glutamate derivative is L-glutamate ethyl ester hydrochloride.

[0010] The above technical solution combines N-lauroyl-L-glutamate sodium salt and L-glutamate ethyl ester hydrochloride. The critical micelle concentration and protonation equilibrium constant of the two are strictly matched within the pH window of 9.0-10.0, which increases the aspect ratio of fibrous micelles to ≥15:1 and compresses the tip size to 20-40nm, significantly enhancing the targeted penetration ability. At the same time, the pKa2 of L-glutamate ethyl ester hydrochloride falls precisely within the cleaning pH range, ensuring the optimal dynamic balance of protonation-deprotonation, driving micelle deformation and resin hydrolysis to proceed simultaneously and efficiently, thus improving cleaning efficiency.

[0011] Preferably, the corrosion inhibitor is any one of benzotriazole, methylbenzotriazole, 2-mercaptobenzothiazole, and 2-mercaptobenzimidazole.

[0012] Preferably, the mass ratio of trisodium ethylenediamine disuccinate to sodium gluconate is 1:(1.2-1.8).

[0013] Preferably, the co-chelation constant logK (Ca) of the trisodium ethylenediamine disuccinate is... 2+ ) ≥10.2; the co-chelation constant of the sodium gluconate is logK(Ca 2+ ≥8.7.

[0014] In the above technical solution, trisodium ethylenediaminedisuccinate and sodium gluconate form an optimal dual-ligand synergistic chelation configuration within this ratio range, which is beneficial for Ca... 2+ The chelation constant logK ≥ 10.2, for Fe 3+ With a chelation constant logK ≥ 8.7, it achieves broad-spectrum and efficient capture of multivalent metal ions, removing free Ca from the cleaning solution. 2+ / Fe 3+The concentration is controlled at <0.1ppm; at the same time, this ratio can ensure that the metal ion complexation rate is >95%, effectively blocking the redeposition path of metal ions during the drying process, eliminating FA end face spot residue, and ensuring the reliability of optical coupling.

[0015] Preferably, the FA fiber array ultrasonic-specific weak alkaline cleaning agent further comprises 0.3-0.8 wt% polyether L64 and 0.1-0.4 wt% hydroxypropyl methylcellulose.

[0016] The above technical solution, by adding polyether L64, can reduce the surface tension of the liquid film, accelerate the spreading and evaporation of the thin liquid film, and achieve rapid drying without water stains; by adding hydroxypropyl methylcellulose, micelle aggregation and deactivation can be inhibited. Combined with online filtration of 0.05-0.15μm ceramic membrane, the cleaning solution can be recycled to meet the needs of continuous production line operation and reduce cleaning costs.

[0017] Secondly, this application provides a method for preparing a weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber optic arrays, including the following steps: S1: Add 50-80% of the total amount of deionized water to the preparation container; S2: Add trisodium ethylenediamine disuccinate, sodium gluconate and corrosion inhibitor sequentially under stirring conditions, and stir until completely dissolved to obtain the first mixture; S3: Add amphoteric N-acylglutamate sodium and glutamate derivative to the first mixture, and continue stirring until uniform and transparent to obtain the second mixture; then adjust the pH of the second mixture to 9.0-10.0 with citric acid or triethanolamine; S4: Add deionized water to the remaining amount, stir well, and you will get the FA fiber optic array ultrasonic special weak alkaline cleaning agent.

[0018] Preferably, step S3 further includes, after obtaining the second mixture, adding polyether L64 and hydroxypropyl methylcellulose and stirring until completely dissolved, and then adjusting the pH value.

[0019] The above preparation method involves adding each component sequentially through stepwise dissolution, ensuring that each component is fully dissolved under stirring conditions before introducing the next component. This effectively avoids problems such as precipitation, aggregation, or incomplete reaction caused by differences in solubility or excessively high local concentrations of each component, thus guaranteeing the uniform formation and stability of the pH-responsive fibrous micelle system.

[0020] Thirdly, this application provides a cleaning method for FA fiber arrays, using a weakly alkaline ultrasonic cleaning agent specifically for FA fiber arrays, at an ultrasonic power density of 0.3-0.6 W / cm². 2 Clean for 60-90 seconds at a frequency of 40kHz and a temperature of 35-45℃.

[0021] Preferably, when the FA fiber array ultrasonic-specific weak alkaline cleaning agent is used for continuous production line operation, a 0.05-0.15μm ceramic membrane is used to filter the cleaning solution online to remove solid particulate dirt that is detached during the cleaning process, and the filtered cleaning solution is returned to the cleaning tank for recycling.

[0022] The above cleaning method matches the ultrasonic parameters with the oscillation frequency of the fibrous micelles in the cleaning agent, enhancing the mechanical stripping efficiency of the micelles at the dirt-substrate interface and achieving high-efficiency cleaning. When used in continuous production line operations, online filtration with a ceramic membrane can remove stripped solid particles of dirt in real time, preventing dirt re-adhesion. Combined with the thickening and stabilizing effect of hydroxypropyl methylcellulose in the cleaning agent, it effectively inhibits the aggregation and deactivation of micelles during cyclic shearing, ensuring that the micelle morphology stability is >92% and the cumulative metal ion concentration is <0.3ppm after ≥20 batches of cleaning solution recycling. This meets the requirements of continuous production line operations, significantly extending the service life of the cleaning solution and reducing unit cleaning costs.

[0023] In summary, this application has the following beneficial effects: 1. This application constructs a pH-responsive fibrous micelle system by combining amphoteric N-acylglutamate sodium salt and glutamate derivatives under pH conditions of 9.0-10.0. The number average particle size is 42.3 nm, and the PDI is 0.132. Its nanoscale tip can target and penetrate the micron-sized gaps in the FA array, disrupting the adhesion of complex dirt from the inside, achieving a complex dirt removal rate of over 99.5%. Furthermore, through the synergistic chelation of trisodium ethylenediamine disuccinate and sodium gluconate dual ligands, free Ca2+ is removed. 2+ / Fe 3+ By controlling the concentration to <0.1ppm, the redeposition of metal ions is blocked. Combined with benzotriazole corrosion inhibition protection, the Ra change on the end face is <0.02nm and the corrosion depth is <0.5nm, achieving 100% non-destructive treatment of the substrate.

[0024] 2. The cleaning method of this application operates at an ultrasonic power of 0.3-0.6 W / cm². 2 Cleaning can be completed in 60-90 seconds at 35-45℃. The polyether-containing L64 solution can achieve rapid low-temperature drying with 40℃ hot air drying for 60 seconds and a water contact angle of <5°. The hydroxypropyl methylcellulose-containing solution, combined with online ceramic membrane filtration, allows for the recycling of cleaning solution for ≥20 batches, reducing unit cleaning costs by >35%. All components are free of halogens and phosphorus compounds, with VOC <50g / L and a biodegradability rate >92%, meeting environmental regulations. Detailed Implementation

[0025] The technical solution of this application is further illustrated by specific embodiments below. These specific embodiments do not represent a limitation on the scope of protection of this application. Any non-essential modifications and adjustments made by others based on the concept of this application still fall within the scope of protection of this application.

[0026] Unless otherwise specified, the experimental methods shown in the following examples are conventional methods. All reagents and materials shown are commercially available products.

[0027] L-Glutamic acid ethyl ester hydrochloride, pKa2=9.17; N-lauroyl-L-glutamate sodium sodium purity ≥99.0wt%, critical micelle concentration at pH 9.5 is 0.8-1.2 mmol / L; polyether L64 average molecular weight is 2900, HLB value is 13.0; hydroxypropyl methylcellulose viscosity is 100-150 mPa·s.

[0028] The present application will be further described in detail below with reference to embodiments and comparative examples. Example

[0029] Example 1 A method for preparing a weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber optic arrays includes the following steps: S1: Add 500g of deionized water to the preparation container; S2: Add trisodium ethylenediamine disuccinate, sodium gluconate and corrosion inhibitor sequentially under stirring conditions, and stir until completely dissolved to obtain the first mixture; S3: Add amphoteric N-acylglutamate sodium and glutamate derivative to the first mixture, and continue stirring until uniform and transparent to obtain the second mixture; then adjust the pH of the second mixture with citric acid or triethanolamine; S4: Add deionized water to a total weight of 1000g, stir well, and the FA fiber array ultrasonic special weak alkaline cleaning agent is obtained.

[0030] The composition and dosage of the special weak alkaline cleaning agent are shown in Table 1:

[0031] Examples 2-5 The difference from Example 1 is that the dosage of the special weak alkaline cleaning agent is shown in Table 1.

[0032] Example 6 The difference from Example 1 is that: a method for preparing a weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber optic arrays includes the following steps: S1: Add 500g of deionized water to the preparation container; S2: Add trisodium ethylenediamine disuccinate, sodium gluconate and corrosion inhibitor sequentially under stirring conditions, and stir until completely dissolved to obtain the first mixture; S3: Add amphoteric N-acylglutamate sodium and glutamate derivative to the first mixture, and continue stirring until uniform and transparent to obtain the second mixture; then add polyether L64 and hydroxypropyl methylcellulose and stir until completely dissolved, and then adjust the pH of the second mixture to 9.5 with citric acid or triethanolamine; S4: Add deionized water to a total weight of 1000g, stir well, and the FA fiber array ultrasonic special weak alkaline cleaning agent is obtained.

[0033] The composition and dosage of the special weak alkaline cleaning agent are shown in Table 2:

[0034] Examples 7-10 The difference from Example 6 is that the dosage of the special weak alkaline cleaning agent is shown in Table 2. Application examples

[0035] Application Example 1 The FA fiber array to be cleaned was placed in the cleaning agent prepared in Example 1, and the ultrasonic power density was 0.5 W / cm². 2 Clean for 75 seconds at a frequency of 40kHz and a temperature of 40℃.

[0036] Application Example 2-10 The difference from Application Example 1 is that the cleaning agents were prepared in accordance with the methods of Examples 2-10.

[0037] Application Example 11 The difference from Application Example 1 is that the ultrasonic power density is 0.3 W / cm². 2 Clean for 90 seconds at a frequency of 40kHz and a temperature of 45℃.

[0038] Application Example 12 The difference from Application Example 1 is that the ultrasonic power density is 0.6 W / cm². 2 Clean for 60 seconds at a frequency of 40kHz and a temperature of 35℃.

[0039] Application Example 13 The FA fiber array to be cleaned was placed in the cleaning agent prepared in Example 6, and the ultrasonic power density was 0.5 W / cm². 2 The cleaning solution was subjected to a frequency of 40kHz and a temperature of 40℃ for 75 seconds. After cleaning, the cleaning solution was filtered online through a 0.1μm ceramic membrane to remove the detached solid particles and was then returned to the cleaning tank. This process was repeated, with samples taken after every 5 batches of cleaning to test the performance of the cleaning solution; the cleaning solution was reused for 25 batches.

[0040] Comparative Example Comparative Example 1 The difference from Application Example 6 is that no glutamic acid derivative is added, while the remaining components, dosages, and cleaning methods are exactly the same as in Application Example 6.

[0041] Comparative Example 2 The difference from Application Example 6 is that N-lauroyl-L-glutamate sodium sodium is replaced with an equal amount of sodium dodecylbenzenesulfonate (68g), and L-glutamate ethyl ester hydrochloride is not added. The remaining components, dosages, and cleaning methods are exactly the same as in Application Example 6.

[0042] Comparative Example 3 The difference from Application Example 6 is that trisodium ethylenediamine disuccinate and sodium gluconate are not added, while the remaining components, dosages, and cleaning methods are exactly the same as in Application Example 6.

[0043] Comparative Example 4 The difference from Application Example 6 is that sodium gluconate is not added, and the amount of trisodium ethylenediaminedisuccinate is adjusted to 65g (keeping the total amount of chelating agent equivalent to the total amount of trisodium ethylenediaminedisuccinate + sodium gluconate in Example 6, which is 63g). The remaining components, amounts, and cleaning methods are exactly the same as in Application Example 6.

[0044] Comparative Example 5 The difference from Application Example 6 is that benzotriazole is not added, but the remaining components, dosages, and cleaning methods are exactly the same as in Application Example 6.

[0045] Comparative Example 6 The difference from Example 1 is that the pH value was adjusted to 6.5, while the other components and amounts were exactly the same as in Example 1.

[0046] Comparative Example 7 The difference from Example 1 is that the pH value was adjusted to 10.2, while the other components and amounts were exactly the same as in Example 1.

[0047] Performance testing The following performance tests were conducted on the FA fiber arrays cleaned according to the methods of Case 1-13 and Comparative Examples 1-7.

[0048]

[0049] The measurement results are shown in Tables 4, 5 and 6.

[0050]

[0051]

[0052]

[0053] As shown in Table 4, the performance test results indicate that the composite fouling removal rate in Application Examples 1-12 all reached over 98.5%; the change in end-face Ra value was all <0.03nm, meeting the target of <0.02nm; the metal ion concentration was all <0.15ppm, and in Application Examples 4 and 6-10, the metal ion concentration was all <0.1ppm. The corrosion depth was all <0.6nm, meeting the Telcordia GR-1209-CORE standard. Application Examples 6-9, containing polyether L64, showed a water contact angle <5° after 60s of hot air drying at 40℃, demonstrating excellent low-temperature rapid drying performance; Application Examples 6-8 and 10, containing HPMC, also exhibited excellent drying performance. In Application Examples 11-12, the composite fouling removal rate remained above 98.5% despite changes in ultrasonic parameters.

[0054] Analysis of Comparative Example 1: The component lacked a glutamic acid derivative, resulting in a clearance rate of only 71.2%, significantly lower than the 99.6% of Application Example 6. The absence of the glutamic acid derivative prevented the formation of pH-responsive fibrous micelles, causing the micelle system to lose its targeted penetration ability. Cleaning relied solely on the emulsifying effect of conventional surfactants, resulting in insufficient penetration into the gaps of embedded grinding powder and resin residue, and inadequate destruction of internal adhesion. Water stains / spots appeared after drying. This result demonstrates that the glutamic acid derivative is a key component in constructing a pH-responsive fibrous micelle system, and the strict matching relationship between its pKa2=9.17 and the pH 9.0-10.0 cleaning window is one of the core technical features of this invention.

[0055] Comparative Example 2 Analysis: Replacing N-lauroyl-L-glutamate with sodium dodecylbenzenesulfonate resulted in a clearance rate of only 65.8%, the worst among all comparative examples. Sodium dodecylbenzenesulfonate is a conventional anionic surfactant and lacks pH-responsive micelle deformation capabilities, failing to form high aspect ratio fibrous micelles and thus lacking targeted penetration into the micron-sized gaps of the FA array. Furthermore, LAS lacks the ability to selectively hydrolyze resin residues under weakly alkaline conditions. Water stains / spots were evident after drying. These results demonstrate that the chain length structure and pH-responsive micelle formation ability of amphoteric N-acylglutamate are irreplaceable.

[0056] Comparative Example 3 Analysis: The component did not contain trisodium ethylenediamine disuccinate or sodium gluconate, and was a chelating agent-free system; the removal rate was 81.5%, and the Ca in the rinsing water was low. 2+ Up to 0.45 ppm, Fe 3+ The concentration reached 0.52 ppm, and obvious water stains / spots appeared after drying. The system without chelating agents could not effectively complex free metal ions in the rinsing water, causing ions to deposit on the FA end face during drying, forming spots. Simultaneously, residual metal ions may affect the adhesion of subsequent coatings. These results demonstrate that the dual-ligand synergistic chelating system composed of trisodium ethylenediaminedisuccinate and sodium gluconate is a necessary condition for controlling the metal ion concentration to <0.1 ppm; neither can be omitted.

[0057] Comparative Example 4 Analysis: The component only contained trisodium ethylenediaminedisuccinate, making it a single chelating agent system. The removal rate was 89.6%, and the Ca in the rinsing water was... 2+ Up to 0.18 ppm, Fe 3+ The concentration reached 0.20 ppm, and water stains / spots remained after drying. The broad-spectrum capture ability of trisodium ethylenediaminedisuccinate as a single chelating agent was insufficient for polyvalent metal ions. Trisodium ethylenediaminedisuccinate for Ca... 2+ The chelation constant logK ≥ 10.2, but for Fe... 3+ The synergistic capture of metal ions requires the cooperation of sodium gluconate (logK≥8.7) to achieve efficient synergy. A single chelating agent system cannot achieve the synergistic effect of the two ligands. This result demonstrates that the mass ratio of trisodium ethylenediaminedisuccinate to sodium gluconate of 1:(1.2-1.8) and the synergistic chelation mechanism of the two ligands are key technical characteristics ensuring the broad-spectrum and efficient capture of metal ions.

[0058] Comparative Example 5 analysis: Without corrosion inhibitors or benzotriazole, the removal rate was 98.2%, close to the 99.6% of Application Example 6. However, the corrosion depth reached 3.2 nm, and the Ra change reached 0.15 nm, significantly higher than <0.5 nm and <0.02 nm in Application Example 6. Although the cleaning effect itself was not significantly affected, the metal positioning grooves in the FA array still underwent some corrosion under weakly alkaline conditions without corrosion inhibitors, resulting in impaired end-face optical properties and failing to meet the Telcordia GR-1209-CORE standard. Drying performance was unaffected. These results demonstrate that while the addition of corrosion inhibitors such as benzotriazole does not directly affect the cleaning effect, it is crucial for protecting the integrity of the FA array's metal substrate and is an indispensable auxiliary component.

[0059] To quantitatively characterize the size distribution and uniformity of micelles under different pH conditions, dynamic light scattering (DLS) was used to test the hydrodynamic particle size and polydispersity index (PDI) of the system. The test results are shown in Table 5. In the DLS data, the optimal pH=9.5 fiber micelle system had a number-average particle size of 42.3 nm, stably achieving the design target of a tip size ≤50 nm. The average PDI of the system was only 0.132, less than 0.2, indicating that the prepared fibrous micelles had an extremely narrow size distribution, excellent monodispersity, and good system uniformity and stability. The intensity-average particle size reached 1857 nm, corresponding to the micron-level length characteristics of fibers, directly confirming the successful formation of a high aspect ratio one-dimensional fiber structure. In the slightly acidic system (pH 6.5), the number-average particle size reached 1246 nm, and the PDI was 0.476, indicating severe polydispersity. The system contained numerous irregular large particle agglomerations, completely disrupting the ordered assembly structure of the micelles. In the strongly alkaline system (pH 10.5), the particle size decreased significantly, with only nanoscale particles present. The PDI rose to 0.215, size uniformity decreased, and the one-dimensional fiber structure completely disintegrated. The significant differences in particle size and PDI among the three systems fully demonstrate the precise regulatory role of pH on micelle assembly behavior.

[0060] In application example 13, the micelle morphology stability of the cleaning solution remained above 92% during 20 batches of recycling. Thanks to the thickening and stabilizing effect of hydroxypropyl methylcellulose, the removal rate of complex dirt remained above 98.9%, the cumulative concentration of metal ions was controlled below 0.3 ppm, and there were no water stains / spots left after rinsing. This indicates that the cleaning performance of the cleaning solution remained stable within 20 batches and can meet the needs of continuous production line operation.

[0061] The above experimental results show that the FA fiber array ultrasonic-specific weakly alkaline cleaning agent prepared in this application achieves excellent comprehensive cleaning performance through the synergistic effects of a pH-responsive fibrous micelle system, a dual-ligand synergistic chelation system, corrosion inhibition protection, and a weakly alkaline pH window. The cleaning agents in Application Examples 1-12 all achieved a removal rate of over 98.5% for complex contaminants. After cleaning, the Ra value change on the FA fiber end face was less than 0.03 nm, and the corrosion depth of the metal positioning groove was less than 0.6 nm, achieving a balance between efficient cleaning and no damage to the substrate. The Ca in the rinsing water... 2+ / Fe 3+ All concentrations were below 0.15 ppm, and no water stains / spots remained after drying. The cleaning agent containing polyether L64 had a water contact angle of less than 5°, enabling rapid drying at low temperatures. Comparative data further verified the indispensability of the pH-responsive micelle system, the synergistic effect of the double chelating agent, and the corrosion inhibitor. This invention effectively solves the problems of strong alkali corrosion of substrates, excessive VOCs, and metal ion redeposition in existing technologies, while also possessing high permeability, substrate compatibility, and environmental safety, showing promising prospects for industrial application.

[0062] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the present invention, they are protected by patent law.

Claims

1. A weakly alkaline cleaning agent specifically for ultrasonic cleaning of FA fiber optic arrays, characterized in that, It consists of the following components by weight percentage: Sodium amphoteric N-acylglutamate 5.0-8.5 wt%; Glutamic acid derivatives 3.0-6.0 wt%; Trisodium ethylenediaminedisuccinate 1.5-4.0 wt% Sodium gluconate 2.0-5.0 wt%; Corrosion inhibitor 0.2-1.5 wt%; The remainder is deionized water; The glutamic acid derivative is either L-glutamic acid methyl ester hydrochloride or L-glutamic acid ethyl ester hydrochloride; The cleaning agent has a pH value of 9.0-10.

0.

2. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, It consists of the following components by weight percentage: Amphoteric N-acylglutamate sodium salt 6.2-7.8 wt% Glutamic acid derivatives 3.8-5.2 wt%; Trisodium ethylenediaminedisuccinate 2.2-3.0 wt%; Sodium gluconate 3.0-4.0 wt%; Corrosion inhibitor 0.5-1.0 wt%; The remainder is deionized water; The glutamic acid derivative is either L-glutamic acid methyl ester hydrochloride or L-glutamic acid ethyl ester hydrochloride; The cleaning agent has a pH value of 9.2-9.

8.

3. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, The amphoteric N-acylglutamate sodium salt is N-lauroyl-L-glutamate sodium salt, and the glutamate derivative is L-glutamate ethyl ester hydrochloride.

4. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, The corrosion inhibitor is any one of benzotriazole, methylbenzotriazole, 2-mercaptobenzothiazole, and 2-mercaptobenzimidazole.

5. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, The mass ratio of trisodium ethylenediamine disuccinate to sodium gluconate is 1:(1.2-1.8).

6. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, The co-chelation constant logK (Ca) of the trisodium ethylenediamine disuccinate 2+ ) ≥10.2; the co-chelation constant of the sodium gluconate is logK(Ca 2+ ≥8.

7.

7. The weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays according to claim 1, characterized in that, It also contains 0.3-0.8 wt% polyether L64 and 0.1-0.4 wt% hydroxypropyl methylcellulose.

8. A method for preparing a weakly alkaline cleaning agent for ultrasonic cleaning of FA fiber optic arrays as described in any one of claims 1-7, characterized in that, Includes the following steps: S1: Add 50-80% of the total amount of deionized water to the preparation container; S2: Add trisodium ethylenediamine disuccinate, sodium gluconate and corrosion inhibitor sequentially under stirring conditions, and stir until completely dissolved to obtain the first mixture; S3: Add sodium amphoteric N-acylglutamate and glutamate derivative to the first mixture, and continue stirring until uniform and transparent to obtain the second mixture; then adjust the pH of the second mixture to 9.0-10.0 with citric acid or triethanolamine; S4: Add deionized water to the remaining amount, stir evenly, and the FA fiber array ultrasonic special weak alkaline cleaning agent is obtained.

9. The method for preparing the cleaning agent according to claim 8, characterized in that, Step S3 further includes the following steps: after obtaining the second mixture, add polyether L64 and hydroxypropyl methylcellulose and stir until completely dissolved, and then adjust the pH value.

10. A method for cleaning an FA fiber array, characterized in that, Using the cleaning agent described in any one of claims 1-7, at an ultrasonic power density of 0.3-0.6 W / cm³ 2 Clean for 60-90 seconds at a frequency of 40kHz and a temperature of 35-45℃.

Citation Information

Patent Citations

  • Aqueous fiber optic cleaner

    CN101795784B

  • Cleaning agent special for ceramic ferrules for fiber optic connectors

    CN1262629C